The role of knowledge management in administrative reform in Syria A field study on a sample of government institutions operating in the Syrian coast (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the role of knowledge management in administrative reform, by studying the role of knowledge management processes, represented by: acquiring knowledge, storing knowledge, and transferring knowledge in administrative reform. The researchers relied on the descriptive-analytical approach as a general approach to research, where a questionnaire was designed and distributed to an easy sample (400, retrieved 396 valid questionnaires for statistical analysis) of workers at the upper and middle administrative levels in a number of government institutions operating in the Syrian coast, and the researchers used the statistical program Spss26 in conducting statistical characterization and testing research hypotheses. The research found a positive moral effect for the adoption of knowledge management in the administrative reform process, and the order of knowledge management processes in terms of the strength of influence in the administrative reform process, according to the following order: knowledge acquisition, knowledge transfer, and knowledge storage.